Helmet CPAP bundle: A narrative review of practical aspects and nursing interventions to improve patient's comfort. (February 2023) - Lucchini, Alberto; Giani, Marco; Minotti, Dario; Elli, Stefano; Bambi, Stefano
Highlights: Helmet-CPAP requires a Gas Flow > 50 L/min and a manometer to accurately detect the airway pressure. Respiratory filters (HMEF or bacterial filter) placed on the inlet side of the breathing circuit help to reduce noise during helmet CPAP. Using a counterweight fixing system help to improve patient's comfort. Heated humidifiers equipped with NIV software can provide an absolute humidity > 10 mg H2 O/L, without condensation development. Abstract: Background: The application of Continuous Positive Airway Pressure (CPAP) with a helmet is increasing around the world, both inside and outside of the intensive care unit. Current published literature focus's on indications, contraindications and efficiency of Helmet CPAP in differing clinical scenarios. Few reports, summarising the available knowledge concerning technical characteristics and nursing interventions to improve patient's comfort, are available. Aim: To identify the crucial technical aspects in managing patients undergoing Helmet-CPAP, and what nursing interventions may increase comfort. Methods: A narrative literature review of primary research published 2002 onwards. The search strategy comprised an electronic search of three bibliographic databases (Pubmed, Embase, CINAHL). Results: Twenty-three studies met the inclusion criteria and were included in the review. Research primarily originated from Italy. Nine key themes emerged from the review: gas flow management, noise reduction, impact of gas flow and HME filters on delivered FiO2, filtration of exhaled gas / environmental protection, PEEP monitoring, airway pressure monitoring, active humidification of gas flow, helmet fixation and tips to implement awake prone position during Helmet-CPAP. Conclusions: A Helmet-CPAP check-list has been made of nine key interventions based on the available evidence regarding system set up, monitoring and management. Implementation of this check-list may help nurses and physicians to increase the comfort of patients treated with Helmet CPAP and enhance their compliance with long-term treatment.